Australian Law Postgraduate Network final report. - Colbran, Stephen; Tynan, Belinda (Australian Learning and Teaching Council (ALTC), 2008)
Project Findings: The project designed and implemented the Australian Law Postgraduate Network (ALPN) to benefit all law schools and their postgraduate students through extensive collaboration across the education law sector. Smaller law schools, particularly those in rural and regional areas which do not have a large pool of supervisors, will gain a significant advantage from the network. The project also promoted cross-disciplinary bridges to extend legal research methodologies. Managing law postgraduate students in distributed locations provides leadership in the affordances of 'anytime' and 'anyplace' flexibility enabled by using online technologies. The principles developed in this approach may be readily applied to other disciplines, as well as across international borders. It demonstrates synergies that can be developed by: connecting professional academics in different institutions who have expertise in a student's postgraduate research topic; ensuring students having access to experienced supervisors in their specific area of interest; providing students with an easy-to-locate list of supervisors, supervision records, and topics; improving knowledge and support of alternative research methodologies; encouraging interaction and collaboration between students and supervisors across institutions; and professionally marketing Australian postgraduate research degrees in law to international students. [Publisher website]